The Factors That Influence and Protect Against Power Imbalance in Covert Bullying Among Preadolescent Children at School: A Thematic Analysis - Nelson, Helen; Burns, Sharyn; Kendall, Garth; Schonert-Reichl, K. (Sage Publications, 2018)
In this article, the perceptions of preadolescent children (ages 9–11) regarding factors that influence and protect against power imbalance associated with covert aggression and bullying are explored. In aggression research, the term covert has been typically used to describe relational, indirect, and social acts of aggression that are hidden. These behaviors contrast with overt physical and verbal aggression. Children have previously conveyed their belief that covert aggression is harmful because adults do not see it even though children, themselves, are aware. We used focus groups to explore children’s understanding of covert aggression and to identify children’s experience and perception of adult support in relation to bullying. Thematic analysis supported the definition of covert aggression as that which is intentionally hidden from adults. Friendship, social exclusion, and secret from teacher were identified as factors that influence power imbalance, while support from friends and adult support protected against power imbalance.